Nitrogen biotransformation: its ecological control and risk assessment in soil - Ferisman Tindaon; Gero Benckiser (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
The Haber-Bosch (H-B) process, which enables the industrial production of ammonia from nitrogen and hydrogen, fundamentally changed food production. This process is crucial for synthesizing nitrogen-based fertilizers, which are essential for boosting crop yields and supporting the world's growing population. Monoculture farming, particularly when combined with high nitrogen input, poses significant environmental risks. It leads to soil degradation, increased vulnerability to pests and diseases, and water pollution. Reliance on synthetic fertilizers to offset nutrient depletion further worsens these problems. The question explores whether current analytical methods adequately identify and evaluate the side effects of urease (UI), nitrification (NI), and denitrification (DI) inhibitors used in nitrogen management strategies for high-yield monoculture farming. While inhibitors are designed to improve nitrogen use efficiency and reduce losses, their effectiveness must be weighed against their unintended consequences, necessitating the development of more comprehensive and holistic analytical approaches that better balance productivity and environmental protection. This research focuses on how different nitrogen fertilizer strategies, along with pesticide use, affect non-target organisms in ecosystems. It specifically examines the impacts of urea, nitrate manipulation, and stabilized nitrogen fertilizers like urease inhibitors (UI), nitrification inhibitors (NI), and dual inhibitors (DI) on ecological balance. The study also examines the broader environmental implications of these practices, including nitrogen loss and greenhouse gas emissions.  It highlights how these agrochemicals can affect wild plants, pollinators, and other non-target species, potentially disrupting ecosystem functions.